The Sky is Your Laboratory Advanced Astronomy Projects for Amateurs - Buchheim, Robert; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Praxis, 2007)
For the experienced amateur astronomer who is wondering if there is something useful, valuable, and permanent that can be done with his or her observational skills, the answer is, "Yes, you can!" This is the book for the experienced amateur astronomer who is ready to take a new step in his or her astronomical journey. Unfortunately, there is no modern text that points curious amateur astronomers to the research possibilities that are open to them. At the 2006 meeting of the Society for Astronomical Sciences, quite a few participants agreed that the lack of such a text was a serious gap in the astronomical book market, and that this gap is impeding their efforts to encourage more amateur astronomers to get involved in research collaborations. This book will fill that gap, and enable more amateur astronomers to add research-type studies to their pursuit of the hobby. Written by an astronomer who is well known amongst the amateur and professional community for the skill and quality of his work, this book describes a wide range of research areas where amateurs are gathering new scientific data that is utilized by professional astronomers. For each research area, the book provides a concise explanation of the purpose and value of the amateurs’ observations, a description of the equipment that is needed, specific observing procedures, complete data reduction instructions, and an explanation of how, and where, to submit results so that they will be available to the professional users.
Meteor Studies -- Visual meteor counts of major meteor showers -- Characterization of minor meteor showers -- Characterizing Sporadic meteors, and discovering unrecognized showers -- Automating your Meteor Observations -- Radio Meteor Monitoring -- Additional Reading and Resources -- Occultations -- Lunar Occultation Timing -- Grazing Lunar Occultations -- Asteroid Occultation Timing -- International Occultation Timing Association -- Additional Reading and Resources -- Visual Observing -- Variable Star Observing -- AAVSO -- CCD Photometry -- General Principles of Aperture Photometry -- Selection of Comp Stars -- Software Packages for Photometry -- Absolute vs. Differential Photometry -- CCD Photometry of Variable Stars -- Determining Asteroid Lightcurves -- Signal, Noise, and Photometric Accuracy -- Extra-Solar Planet Transits -- Absolute Photometry on the B-V-R system -- Asteroid Phase Curves -- CCD Astrometry.-Basic Principles of Astrometry -- Equipment needed -- Making the Observations -- Reducing and Analyzing your Results -- Asteroid astrometry -- Binary Stars: Separation and Position Angle -- Discovery projects -- Lunar Meteor Impacts -- Asteroid Hunting and Discovery -- Comet Hunting -- Nova and Supernova Hunting -- Nova Search -- Supernova Search -- Serendipitous discoveries -- Some Notes on Time -- Some Background on Astrometric Concepts -- The scientist's record book.
Keywords: Astronomy; Astrophysics; Observations, Astronomical; Astronomy—Observations.; Popular Science in Astronomy; Astronomy, Astrophysics and Cosmology; Astronomy, Observations and Techniques